Fertility potential in men with a history of congenital undescended testes: a long‐term follow‐up study. (23rd October 2012) - van, J.; Kranse, R.; de, S. M. P. F.; Hendriks, A. E. J.; de, F. H.; Bangma, C. H.; Hazebroek, F. W. J.; Dohle, G. R.
Abstract Men with a history of congenital undescended testes (UDT) have an increased risk of fertility problems. Despite no definitive proof, current guidelines recommend early surgical intervention because this may have a positive effect on future fertility potential by preventing degenerative changes of the testes in early life. Also surgical intervention facilitates observability of the testes in view of possible malignancy. We evaluated testicular function in adult men with previous UDT treated at different ages before puberty. A long‐term follow‐up study of men with previous UDT was performed. Andrological evaluation included medical history taking, physical examination, scrotal ultrasound, determination of reproductive hormones, and semen analysis. Findings were compared with those of a control group of men with normal testicular descent. The influence of age at orchiopexy on future fertility parameters was evaluated in a multivariate regression analysis. 62 men were included of whom seven had had bilateral UDT. Twenty‐four patients had had their orchiopexy before the age of 24 months of whom eight men had it before 12 months of age. Forty‐eight men had had unsuccessful luteinizing‐hormone‐releasing‐hormone (LHRH) nasal spray treatment during childhood, whereas 14 of 24 men operated before 24 months of age had not received LHRH treatment before orchiopexy. Fertility potential in men with a history of UDT is compromised in comparison with controls. We could not detect any influence of age at orchiopexy on fertility parameters. However, the number of patients operated before the age of 12 months is limited. This study does not support the assumption that early orchiopexy results in better fertility potential.